Energie della e per la città International Smart Cities School 2020 - Mundula, Luigi (Tomorrow's cities, 2021)
This volume collects part of the lectures and key-notes given at the 2020 edition of the International Smart City School: imagination, planning, governance and tools. The year's theme, "energies of and for the city," was addressed, as in the school's founding idea, from a multidisciplinary perspective by delving into both possible policy scenarios and more strictly technical aspects. Thus emerges a vision of a city that, to orient its development in terms of smartness, sustainability and resilience, must necessarily combine nature and technology, economy and culture, social cohesion and entrepreneurship, innovation and tradition. In this framework, the Sustainable Development Goal's (SDG's) outlined in the United Nations 2030 Agenda and the ways cities can contribute to their achievement occupy a prominent place. Indeed, the technologies available today make it possible to achieve these goals as well as to respond effectively to the challenges that cities, in their capacity as the main attractors of the world's population, will face thanks to their ability to succeed, when properly implemented, in interpreting the new themes of economic development (circularity, sharing, openess) in a way that ensures equal opportunities for all, intergenerationally and intragenerationally.